Using Synthetic Biology to Engineer Spatial Patterns. Issue 4 (17th December 2018) - Santos‐Moreno, Javier; Schaerli, Yolanda
Abstract: Synthetic biology has emerged as a multidisciplinary field that provides new tools and approaches to address longstanding problems in biology. It integrates knowledge from biology, engineering, mathematics, and biophysics to build—rather than to simply observe and perturb—biological systems that emulate natural counterparts or display novel properties. The interface between synthetic and developmental biology has greatly benefitted both fields and allowed to address questions that would remain challenging with classical approaches due to the intrinsic complexity and essentiality of developmental processes. This Progress Report provides an overview of how synthetic biology can help to understand a process that is crucial for the development of multicellular organisms: pattern formation. It reviews the major mechanisms of genetically encoded synthetic systems that have been engineered to establish spatial patterns at the population level. Limitations, challenges, applications, and potential opportunities of synthetic pattern formation are also discussed. Abstract : The use of synthetic biology tools and approaches for spatial pattern formation allows researchers to build artificial systems that emulate natural patterns, to explore non‐natural designs and to produce engineered patterns with potential applications. This Progress Report reviews how genetically encoded synthetic systems have been engineered to establish spatial patterns.